2014
DOI: 10.1007/s00253-014-5942-x
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia- and methane-oxidizing microorganisms in high-altitude wetland sediments and adjacent agricultural soils

Abstract: Ammonia oxidation is known to be carried out by ammonia-oxidizing bacteria (AOB) and archaea (AOA), while methanotrophs (methane-oxidizing bacteria (MOB)) play an important role in mitigating methane emissions from the environment. However, the difference of AOA, AOB, and MOB distribution in wetland sediment and adjacent upland soil remains unclear. The present study investigated the abundances and community structures of AOA, AOB, and MOB in sediments of a high-altitude freshwater wetland in Yunnan Province (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
2

Year Published

2015
2015
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 48 publications
0
22
2
Order By: Relevance
“…A few previous studies showed the numerical dominance of AOA over AOB in plateau grassland soils, agricultural soils, and forest soils (Chen et al 2013;Ding et al 2014;Wang et al 2012;Yang et al 2014;Zheng et al 2014). In this study, AOA outnumbered AOB in most of the studied plateau soils, suggesting that AOA might play a more important role in ammonia oxidation.…”
Section: Soil Aoa and Aob Abundancecontrasting
confidence: 42%
See 4 more Smart Citations
“…A few previous studies showed the numerical dominance of AOA over AOB in plateau grassland soils, agricultural soils, and forest soils (Chen et al 2013;Ding et al 2014;Wang et al 2012;Yang et al 2014;Zheng et al 2014). In this study, AOA outnumbered AOB in most of the studied plateau soils, suggesting that AOA might play a more important role in ammonia oxidation.…”
Section: Soil Aoa and Aob Abundancecontrasting
confidence: 42%
“…Wang et al (2014a) revealed a marked difference in both AOA and AOB community composition in reed-planted riparian soil, bare riparian soil, and maize-planted agricultural soil. Yang et al (2014) also showed a large shift in both AOA and AOB community composition in rice, cabbage, and garlic soils in the Yunnan Plateau. Moreover, Zhao et al (2015) found that AOB community composition was more sensitive to the land use regimes than AOA, while Meyer et al (2014) suggested that, compared with AOB, AOA community composition was responsive to land use intensity.…”
Section: Soil Aoa and Aob Community Diversity And Structurementioning
confidence: 93%
See 3 more Smart Citations